2017
DOI: 10.1016/j.njas.2017.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Tree management and environmental conditions affect coffee (Coffea arabica L.) bean quality

Abstract: Coffees with specific taste and quality fetch higher prices. Although coffee plays a dominant role in the Ethiopian national economy, the country's coffee industry is generally characterized by low productivity and low quality. To address this issue, this study analysed the interactive effect of shade and nitrogen supply, fruit thinning and genotype by environment interactions on different coffee quality attributes. Organoleptic bean quality attributes declined with increase in radiation when nitrogen supply w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 34 publications
(65 reference statements)
3
36
0
3
Order By: Relevance
“…Penelitian pengaruh perbedaan faktor genetik (perbedaan kultivar) dan faktor lingkungan terhadap pertumbuhan dan hasil tanaman kopi telah banyak dilakukan. Hasilnya menunjukkan bahwa faktor genetik dan sebagian faktor lingkungan tumbuh, seperti ketinggian tempat tumbuh, baik dalam bentuk faktor tunggal maupun interaksinya, merupakan faktor yang berpengaruh nyata terhadap produksi, mutu fisik dan kimia biji, serta mutu seduhan kopi (DaMatta, Ronchi, Maestri, & Barros, 2007;Kathurima, Gichimu, Kenji, Muhoho, & Boulanger, 2009;Barbosa et al, 2012;Sualeh, Endris, & Mohammed, 2014;Towaha, Aunillah, Purwanto, & Supriadi, 2014;Randriani & Wardiana, 2015;Towaha, Purwanto, & Supriadi, 2015;Ferreira, Queiroz, Silvac, Tomaz, & Corrêa, 2016;Toledo, Pezza, Pezza, & Toci, 2016;Bote & Jan, 2017).…”
Section: Pendahuluanunclassified
“…Penelitian pengaruh perbedaan faktor genetik (perbedaan kultivar) dan faktor lingkungan terhadap pertumbuhan dan hasil tanaman kopi telah banyak dilakukan. Hasilnya menunjukkan bahwa faktor genetik dan sebagian faktor lingkungan tumbuh, seperti ketinggian tempat tumbuh, baik dalam bentuk faktor tunggal maupun interaksinya, merupakan faktor yang berpengaruh nyata terhadap produksi, mutu fisik dan kimia biji, serta mutu seduhan kopi (DaMatta, Ronchi, Maestri, & Barros, 2007;Kathurima, Gichimu, Kenji, Muhoho, & Boulanger, 2009;Barbosa et al, 2012;Sualeh, Endris, & Mohammed, 2014;Towaha, Aunillah, Purwanto, & Supriadi, 2014;Randriani & Wardiana, 2015;Towaha, Purwanto, & Supriadi, 2015;Ferreira, Queiroz, Silvac, Tomaz, & Corrêa, 2016;Toledo, Pezza, Pezza, & Toci, 2016;Bote & Jan, 2017).…”
Section: Pendahuluanunclassified
“…These may, furthermore, contribute to the complexity of factors determining coffee growth. The complexity of various factors to influence the morphology character of coffee in specific environmental condition has been suggested (De Camargo, 2010;Bote & Vos, 2017;Workie & Debella, 2018). Their level is getting higher as a response to environment also depending on the growth stage of coffee (Adams et al, 2001;Cheng et al, 2016).…”
Section: Qualitative Characteristicsmentioning
confidence: 99%
“…It is suggested that this variation may be resulted from the inseparable factor, i.e. environmental conditions, agronomic practices, and crop genotypes (Wintgens, 2004;Bosselman et al, 2009;De Camargo, 2010;Bote & Vos, 2017;Workie & Debella, 2018), as all these processes may work together to determine coffee characteristics in different sites.…”
Section: Quantitative Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations